Managers’ Characteristics and Employee Productivity - Hunik Sri Runing Sawitri; Salamah Wahyuni; Sinto Sunaryo (Universitas Sebelas Maret, 2016)
We investigate the effect of top management characteristics on employee productivity. Arguably, the presence of encouraging managers will motivate employee to perform better in term of productivity. We use archival data of Indonesian firms to test our hypothesis. Some demographic factors are employed to measure managers’ characteristics. Surprisingly, our results reveal that firms with more educated managers have lower employee productivity. However, we do not find evidence on the effect of managers’ age and tenure on employee productivity.